PERILAKU AGRESI PESERTA DIDIK DI SMPN 3 X KOTO SINGKARAK KABUPATEN SOLOK - Tizia, Rinda Bimei; Syarif, Mellyarti; Gusneli, Gusneli (Bimbingan dan Konseling, 2014)
The background of this research based on hardness which happen to students in the school. The purpose of this research to describe, (1) aggression behavior of student phisically, (2) aggression behavior of student psychologically. This research is a Descriptive qualitative research. The chousing sample use snowball sampling technique. This research three students of class XII as the key informans who have aggression behavior and 3 students ajain as addiny informan also two BK teachers in that school. The data is collected by interview, observation, and documentasion. This data is measured by triangulation after that next to take conclusion. The result of this research shows that 1) aggression behavior of students phisically such as phisic, figh attach each school. Each ridicule. Between students to other students and one of them reply and do not accept the behavior of their friends so students reply with hit their friend who ridicule or mocking the students before. Meanwhile (2) aggression behavior of student psychologically happen each ostracizing, joking, sayins dirti word and humiliate. This research is suggested to students, BKâs teacher, charman of school and all personil in school and also for researcher.